Management of congenital urogenital and perineal vascular malformations: correlation of clinical findings with diagnostic imaging for treatment decision = Management von kongenitalen Gefäßmalformationen des Urogenitaltraktes und der Perinealregion: Korrelation von Klinik und diagnostischer Bildgebung für eine adäquate Therapieentscheidung - Grill, Nadja; Strübing, Felix; Weiß, Christel; Schönberg, Stefan; Sadick, Maliha (RöFo, 2024)
Purpose: Analysis of clinical and diagnostic findings in rare urogenital and perineal vascular malformations only occurring in 2-3 % of vascular anomalies with regard to clinical symptoms and treatment decisions. Materials and Methods: All 25 out of 537 patients presenting with congenital urogenital and perineal vascular malformations at our institution from 2014 to 2021 were included. Vascular anomaly classification, anatomical location, clinical symptoms at presentation, diagnostic imaging, and pain intensity were retrospectively assessed from the patient record and therapy management was evaluated. Results: In total, 25 patients (10 females (40 %), 15 males (60 %)), aged 6 to 77 years were included. Diagnoses were: 10 (40 %) venous malformations (VMs), 5 (20 %) lymphatic malformations (LMs) and 10 (40 %) arteriovenous malformations (AVMs). Malformation manifestations were: 12 (32 %) lesser pelvis, 12 (32 %) external genitalia, and 13 (34 %) perineal/gluteal region. One AVM was located in the kidney. The leading clinical symptom was pain. The mean intensity was 6.0/10 for LM, 5.7/10 for VM, and 4.5/10 for AVM. Further major symptoms included physical impairment, local swelling, and skin discoloration. Bleeding complications or sexual dysfunction were rare findings. Patients with VM reported significantly more symptoms than patients with AVM (p = 0.0129). In 13 patients (52 %) minimally invasive therapy was indicated: 10 (77 %) sclerotherapies and 3 (23 %) transcatheter embolization procedures. Complete symptomatic remission was achieved in 9 (69 %) patients, partial response in 3 (23 %) patients, and 1 patient showed no clinical response to therapy. Follow-up appointments without the need for immediate minimally invasive therapy were significantly more common in patients with AVMs than in patients with VMs (p = 0.0198). Conclusion: To create a higher awareness of congenital urogenital and perineal vascular malformations. Awareness of this rare condition avoids misdiagnosis. Therapy decisions should be symptom-oriented. Emergency intervention is rarely required, even in fast-flow vascular malformations.
Online veröffentlicht: 03.11.2023
Gesehen am 29.02.2024